Role and Regulation of ACC Deaminase Gene in Sinorhizobium meliloti: Is It a Symbiotic, Rhizospheric or Endophytic Gene? - Checcucci, Alice; Azzarello, Elisa; Bazzicalupo, Marco; De Carlo, Anna; Emiliani, Giovanni; Mancuso, Stefano; Spini, Giulia; Viti, Carlo; Mengoni, Alessio (Frontiers in Genetics, 2017)
Plant-associated bacteria exhibit a number of different strategies and specific genes allow bacteria to communicate and metabolically interact with plant tissues. Among the genes found in the genomes of plant-associated bacteria, the gene encoding the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase (acdS) is one of the most diffused. This gene is supposed to be involved in the cleaving of plant-produced ACC, the precursor of the plant stress-hormone ethylene toning down the plant response to infection. However, few reports are present on the actual role in rhizobia, one of the most investigated groups of plant-associated bacteria. In particular, still unclear is the origin and the role of acdS in symbiotic competitiveness and on the selective benefit it may confer to plant symbiotic rhizobia. Here we present a phylogenetic and functional analysis of acdS orthologues in the rhizobium model-species Sinorhizobium meliloti. Results showed that acdS orthologues present in S. meliloti pangenome have polyphyletic origin and likely spread through horizontal gene transfer, mediated by mobile genetic elements. When acdS orthologue from AK83 strain was cloned and assayed in S. meliloti 1021 (lacking acdS), no modulation of plant ethylene levels was detected, as well as no increase in fitness for nodule occupancy was found in the acdS-derivative strain compared to the parental one. Surprisingly, AcdS was shown to confer the ability to utilize formamide and some dipeptides as sole nitrogen source. Finally, acdS was shown to be negatively regulated by a putative leucine-responsive regulator (LrpL) located upstream to acdS sequence (acdR). acdS expression was induced by root exudates of both legumes and non-leguminous plants. We conclude that acdS in S. meliloti is not directly related to symbiotic interaction, but it could likely be involved in the rhizospheric colonization or in the endophytic behavior.